A fluorescence detection method for the determination of β-lactoglobulin in foods. Issue 19 (4th May 2022) - Yang, Jingyi; Zhang, Yong; Lu, Yang
Abstract : A quantum dot–aptamer–graphene oxide probe-based fluorescence method was developed and utilized to detect β-lactoglobulin in real food products. Abstract : A fluorescence detection method based on quantum dot–aptamer–graphene oxide probes (QD–Apt–GO) was developed to detect β-lactoglobulin (β-LG) in foods. When β-LG was present in the samples, it specifically bound to the aptamer, inhibiting the binding of probes to graphene oxide (GO), and the fluorescence of the probes could be detected. When β-LG was not present, the probes could bind to GO through π–π stacking, and the fluorescence was consequently quenched. The detection range of the optimized assay for β-LG detection was 0.36–500 mg L −1 . The limit of detection (LOD) for β-LG was 96.91 μg L −1 . The method was also validated for food sample detection. In the spike and recovery experiments of Neocate amino acid infant formula, infant millet cookies, and infant rice porridge, the recoveries were in the range of 83.33–114.53%, which met the required range of the addition recoveries. At the same time, the results were consistent with those of commercial ELISA kits. Three types of random food products purchased from a local market were analyzed for β-LG via the developed assay and using a commercial ELISA kit. The results showed good accuracy and consistency between the proposed method and the commercial ELISA kit.